(untitled) (Altre Modernità, 2011)
Loshitzky Yosefa, Screening Strangers. Migration and Diaspora in Contemporary European Cinema (Bloomington & Indianapolis, Indiana UP, 2010 pp. 215 ISBN 978 0 253 35453 2) by Nicoletta Vallorani